MEWUJUDKAN PENDIDIKAN BERKUALITAS: DAMPAK PENGEMBANGAN ‎KURIKULUM DI SD AL AZHAR 1 BANDAR LAMPUNG - Asy Syauqi, Icha; Pahrudin, Agus; Jatmiko, Agus; Koderi, Koderi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study examines the impact of curriculum development on the quality of learning and academic growth of students, with a particular focus on Islamic Religious Education (PAI) at SD Al Azhar 1 Bandar Lampung. The importance of foundational education in shaping intellectual, emotional, and character development is paramount. However, several challenges emerge in implementing an ideal curriculum, such as limited technological facilities, insufficient continuous teacher training, and time constraints in applying project-based learning. This qualitative research employs a descriptive approach, with data collected through observations, in-depth interviews, and documentation involving PAI teachers, students, and parents. Findings reveal that the new curriculum positively influences students’ cognitive, affective, and psychomotor aspects, enhancing their understanding and internalization of Islamic values. Furthermore, project-based learning and contextual methods were shown to significantly engage students and foster character building. Nevertheless, challenges such as inadequate technological support and the need for ongoing professional development for teachers were identified as factors that hinder optimal implementation. This research suggests that improvements in technology access, continuous training, and flexible learning schedules are necessary to maximize the curriculum’s effectiveness. The study offers practical recommendations to optimize curriculum application, particularly for Islamic education, and serves as a reference for enhancing educational policy in Indonesia's primary education system.